Strain Assessment of Deep Fascia of the Thigh During Leg Movement: An in situ Study - Sednieva, Yuliia; Viste, Anthony; Naaim, Alexandre; Bruyère-Garnier, Karine; Gras, Laure-Lise (Frontiers in Bioengineering and Biotechnology, 2020)
Fascia is a fibrous connective tissue present all over the body. At the lower leg level, the deep fascia that is overlying muscles of the outer thigh and sheathing them (fascia lata) is involved in various pathologies. However, the understanding and quantification of the mechanisms involved in these sheathing effects are still unclear. The aim of this study is to observe and quantify the strain field of the fascia lata, including the iliotibial tract (ITT), during a passive movement of the knee. Three fresh post-mortem human subjects were studied. To measure hip and knee angles during knee flexion-extension, passive movements from 0° to around 120° were recorded with a motion analysis system and strain fields of the fascia were acquired using digital image correlation. Strains were computed for three areas of the fascia lata: anterior fascia, lateral fascia, and ITT. Mean principal strains showed different strain mechanisms depending on location on the fascia and knee angle. For anterior and lateral fascia, a tension mechanism was mainly observed with major strain greater than minor strain in absolute value. While for the ITT, two strain mechanisms were observed depending on knee movement: tension is observed when the knee is extended relatively to reference position of 47°, however pure shear can be observed when the knee is flexed. In some cases, minor strain can also be higher than major strain in absolute value, suggesting high tissue compression probably due to microstructural fiber rearrangements. This in situ study is the first attempt to quantify the superficial strain field of fascia lata during passive leg movement. The study presents some limitations but provides a step in understanding strain mechanism of the fascia lata during passive knee movement.